Securing the Future of Digital Health: How Blockchain Protects AI-Driven Health Data - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Securing the Future of Digital Health: How Blockchain Protects AI-Driven Health Data The integration of Artificial Intelligence (AI) into healthcare has...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care